FORMATION AND DEVELOPMENT OF SCIENTIFIC SCHOOLS MODEL IN MONOPROFILE HIGHER SCHOOL INSTITUTION - Andrey M. Kal’Yak; Maksim S. Petrenko; Janna V. Nechaeva; Elena S. Shcherbakova (Высшее образование в России)
This article analyzes the model of the formation of research schools and directions in a monoprofile institution (branch) of national research university on an example of the functioning, development and organization of research and teaching work at Novosibirsk Institute of Law (branch) of Tomsk State University. The authors highlight the elements of the model of research schools formation for this type of educational institutions.